Supramolecular Nanostructures of Structurally Defined Graphene Nanoribbons in the Aqueous Phase - Huang, Yinjuan; Dou, Wei-Tao; Xu, Fugui; Ru, Hong-Bo; Gong, Qiuyu; Wu, Dongqing; Yan, Deyue; Tian, He; He, Xiao-Peng; Mai, Yiyong; Feng, Xinliang (Angewandte Chemie International Edition, 2018)
Structurally well-defined graphene nanoribbons (GNRs) have attracted great interest because of their unique optical, electronic, and magnetic properties. However, strong π–π interactions within GNRs result in poor liquid-phase dispersibility, which impedes further investigation of these materials in numerous research areas, including supramolecular self-assembly. Structurally defined GNRs were synthesized by a bottom-up strategy, involving grafting of hydrophilic poly(ethylene oxide) (PEO) chains of different lengths (GNR-PEO). PEO grafting of 42–51 % percent produces GNR-PEO materials with excellent dispersibility in water with high GNR concentrations of up to 0.5 mg mL−1. The “rod–coil” brush-like architecture of GNR-PEO resulted in 1D hierarchical self-assembly behavior in the aqueous phase, leading to the formation of ultralong nanobelts, or spring-like helices, with tunable mean diameters and pitches. In aqueous dispersions the superstructures absorbed in the near-infrared range, which enabled highly efficient conversion of photon energy into thermal energy.
CRIS-Team Scopus Importer:2023-03-20
Keywords: graphene nanoribbons; helices; photothermal conversion; self-assembly; water-dispersible